Shallow-water temperature seasonality in the middle Cretaceous mid-latitude northwestern Pacific - Ichimura, Shunta; Takayanagi, Hideko; Iryu, Yasufumi; Takahashi, Satoshi; Oji, Tatsuo (Frontiers in Marine Science, 2024)
Temperature seasonality during the middle Cretaceous provides vital information about climate dynamics and ecological traits of organisms under the conditions of the “supergreenhouse” Earth. However, sub-annual scale paleotemperature records in the mid-latitude region remain limited. In this study, sclerochronological and stable oxygen isotope (δ18O) analyses of bivalve fossils from the northwestern Pacific (paleolatitude: 44°N) were used to estimate their life history and sub-annual scale temperature patterns of the middle Cretaceous. The materials studied included Cucullaea (Idonearca) delicatostriata and Aphrodina pseudoplana recovered from middle Turonian (middle Cretaceous) shallow marine deposits in Hokkaido, northern Japan. Growth increment width and shell δ18O of C. (I.) delicatostriata revealed that the growth rate was temporally maximized and then minimized, which can be interpreted as representing spring and winter growth, respectively. Approximately 25 fortnightly growth increments occurred within that cycle, suggesting that shell formation proceeded continuously throughout the year. Based on shell δ18O values, shallow-water temperatures from 28°C to 35°C with 7°C seasonality were estimated, under the assumption that seawater δ18O values were annually invariant at −1‰ relative to VSMOW. This temperature seasonality in the middle Cretaceous is more than 5°C smaller than the seasonality of modern shallow-water environments at the same latitudes. These findings, taken together with previous studies of other oceanic regions, suggest that the Northern Hemisphere had low seasonal shallow-water temperature variation of up to 10°C in the middle Cretaceous.